Black zinc particles, and preparation method and application thereof
By using additional materials with specific hardness to blend zinc powder in the dry grinding process, the problem of insufficient stability and corrosion resistance of black zinc pigments in the prior art is solved, and dark and high viscosity is achieved Black zinc pigment, suitable for cathode anti-corrosion coatings.
Patent Information
- Application Number
- CN202380045542.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-19
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to obtain dark and stable black zinc pigments without reducing corrosion resistance. Especially when used in coatings, it is prone to decrease zinc content, viscosity problems and safety hazards.
A black particle composite material is used, containing 58.0-85.0% by weight of elemental zinc or zinc alloy, 4.5-17.0% by weight of Zn-oxide, and an additional material with specific hardness as a grinding additive in the dry grinding process to ensure zinc powder oxidation and blending to form black zinc particles with an average particle size of 5.0-30 μm.
A black zinc pigment with stability and sufficient dark color in salt spray test is achieved, improving corrosion resistance and safety, while reducing production costs.
Smart Images

Figure CN119325493A_ABST
Abstract
Description
[0001] The present invention relates to black zinc particles which can be used in cathode anti-corrosion films.
[0002] Zinc powder is suitable for industrial steel parts, such as automotive parts and electronic parts, and anticorrosive topcoats, thereby protecting elements such as buildings from corrosion. Due to its electrochemical properties, the resin layer containing zinc powder or zinc flakes is used as an anticorrosive layer to prevent steel materials from rusting by sacrificing zinc. The above-mentioned industrial steel parts, such as structural elements of buildings and bridges, and automotive applications and especially screw coatings and structural elements, may need to have a black tone in some applications, because the dark color is in harmony with nature, rather than a shiny electroplated color. In the painting of such elements, especially screws installed in automobiles, most conventional methods are to apply zinc powder or zinc flake paint as a topcoat, dry, then apply a colored topcoat such as a black paint, and dry. Here, a black anticorrosive paint is used, which has a conventional black pigment. However, any scratches of the topcoat are disadvantageously contrasted with the zinc-containing topcoat, which can show a gray to silver color. Therefore, black zinc pigment is needed to reduce this contrast.
[0003] Such a paint has been sought, which improves the blackness and shows anticorrosive properties in a single coating. In order to solve this problem, many technologies for improving the blackness of anticorrosive paints have been studied. For example, JP H0649393A describes a black zinc powder coating composition, which is obtained by mixing 50-86 parts by weight of zinc powder and 1-10 parts by weight of conductive carbon black, relative to 100 parts by weight of a resin-containing coating film forming component. In JP H0222125A, a zinc powder having an oxygen content of 1.0% by weight or less is obtained by quenching zinc vapor, and the zinc powder is placed in an oxygen-containing atmosphere at a temperature of 80-400°C and a pressure of 1-20atm for a period of time. This document discloses a method for preparing a zinc oxide powder for a black pigment by oxidizing the surface, which has an oxygen content of 2.5-18.0% by weight.
[0004] As described above, various methods for improving the blackness of zinc powder paints have been developed. However, for example, a method of mixing a pigment such as carbon black with zinc powder has a problem that the zinc content in the coating film is reduced and the anti-corrosion performance is reduced. In addition, the conventional method for blackening the hue of zinc powder itself is insufficient in terms of blackness.
[0005] DE 10 2014105434A1 discloses a black zinc coating obtained by combining zinc flakes with dark pigments of the spinel type. However, the implementation of this solution is expensive and requires a large amount of dark pigments to obtain a truly dark pigment. However, these pigments may hinder the electrical contact of the zinc flakes, thereby impairing the conductivity. In addition, it may be difficult to adjust the viscosity of the paste containing these mixtures to a suitable range, which reduces the flexibility of coating formulation.
[0006] EP 2173819 A2 also discloses dark metallic pigments obtained by coating metal flakes with a matrix material such as silicon dioxide and a dark pigment with low IR absorption. However, even when zinc is used as the metal flakes, these pigments are difficult to use as anticorrosive pigments, and their preparation is difficult and expensive.
[0007] US 7,021,573 B2 discloses a process for dry grinding of zinc powder using fluorocarbon polymers, wherein no black zinc particles are obtained.
[0008] WO 1999 / 9058274 A1 discloses a dry grinding process using graphite particles as solid lubricant and in the absence of organic lubricants such as long-chain fatty acids. Flake-shaped zinc pigments with high corrosion stability are reported to be obtained, but no black zinc pigments are obtained.
[0009] WO 2021 / 216943 A1 discloses a black zinc pigment, which is composed of elemental zinc, zinc oxide and a lubricant, and can also be used in water-based coatings. However, the document does not disclose a detailed method for preparing such a pigment. The same applicant has a commercially available black zinc pigment product ( Zinc Z2031), but has limited stability in the salt spray test.
[0010] JP 2020105575 A and JP 2021038331 A disclose black zinc pigments obtained by wet grinding using branched fatty acids as lubricants. These lubricants appear to improve oxidation of the zinc particles during grinding. These particles are strongly over-milled when using the preferred milling time, which is greater than when the maximum d of the zinc pigment particle size distribution is reached. 50 The final zinc pigment is very fine and has a d value below 6 μm. 50 When these pigments are finally dried into powders, they may cause safety issues due to their small size. In addition, when these pigments are formulated into coating formulations, they may cause viscosity issues, thereby limiting formulation versatility.
[0011] The same complementary method as these documents is described in JP 2020105338 A, but the grinding time is when the maximum d of the ground zinc pigment is reached. 50 When the time is from 30% to less than 200% of the time, larger zinc flakes are obtained, but they are not black.
[0012] It is therefore an object of the present invention to provide black zinc pigments suitable for cathodic corrosion protection, in particular capable of passing the salt spray test, and having at least the blackness of prior art pigments, but having improved corrosion stability properties.
[0013] This object is achieved by providing a black particle composite material comprising:
[0014] a) Elemental zinc or zinc alloy, containing c Zn,M is in the range of 58.0-85.0 wt % relative to the composite material,
[0015] b) Zn-oxide, and
[0016] c) additional material, wherein the content of the additional material c) is c add is in the range of 4.5-17.0 wt % relative to the total weight of the composite material,
[0017] Components b) and c) are at least partially admixed with the elemental zinc metal a).
[0018] Other preferred embodiments are as described in claims 2-13.
[0019] Another object was to provide a process for preparing these pigments which is inexpensive.
[0020] This object is achieved by providing a method for preparing the black composite material, the method comprising the following steps:
[0021] a) providing a mixture comprising zinc powder, a grinding aid and a lubricating aid in a milling aggregate equipped with milling balls, said grinding aid being prepared from additional material c) or a precursor thereof,
[0022] b) dry grinding the mixture obtained in step a) for a period of time t m , wherein no fluorocarbon polymers are used in the grinding process,
[0023] c) separating the ground mixture from the ground agglomerates, and
[0024] d) Optionally carrying out further steps, such as particle classification and / or pasting.
[0025] Another object is to provide the use of black zinc pigment.
[0026] This object is achieved by using black particle composites as anticorrosion pigments in heavy corrosion protection formulations.
[0027] Details:
[0028] Black zinc particles:
[0029] The black particle composite material of the present invention comprises:
[0030] a) Elemental zinc or zinc alloy, containing c Zn,M is in the range of 58.0-85.0 wt % relative to the composite material,
[0031] b) Zn-oxide, and
[0032] c) additional material, wherein the content of the additional material c) is c add is in the range of 4.5-17.0 wt % relative to the total weight of the composite material,
[0033] And wherein components b) and c) are at least partially admixed with said elemental zinc metal a).
[0034] The black particle composite is in an unformed form and therefore is different from zinc flakes which are generally obtained by dry or wet grinding of zinc powder into a flake shape.
[0035] The term "black" means that the diffuse L*-value measured at D65 / 10° on the flat plate is preferably <36.0, more preferably <35.0, most preferably <34.0. The flat plate is prepared as follows: 56.5 g of black zinc composite material are stirred into 43.5 g of solvent-based silicate varnish (with a solid content of about 55% by weight). Optionally, the viscosity can be adjusted to a range of 30 s to 50 s, which is measured using a flow cup according to DIN 53211, dipropylene glycol (up to 10 g) is added, and the varnish is applied to a metal substrate (steel Q-Panel R46) by a down-draw method (nominal dry film applied: 24 μm, speed 3 cm / min), wherein two applications are made in opposite directions. The flat plate is ventilated at 100° C. for about 30 minutes and baked in an oven at 300° C. for 40 minutes.
[0036] Herein, the term "black particle composite material" may also be used interchangeably with the terms "black zinc" or "black zinc pigment".
[0037] The zinc component may be pure zinc or a zinc alloy. Preferably, the zinc has a purity of 99.99% by weight, more preferably a purity of 99.995% by weight.
[0038] As zinc alloy, preferably an alloy of the general formula (I) is used:
[0039] ZnAl x Mg y M f z (I)
[0040] Wherein, x, y and z represent the weight % content of the corresponding metal, relative to the total content of the alloy. x is in the range of >0 to 10, preferably in the range of 2.5 to 7; y is in the range of ≥0 to 7, preferably in the range of 0.5 to 6; z is in the range of 0 to <2.5, preferably in the range of 0.01 to 0.5, more preferably in the range of 0.02 to 0.1. M f represents other optional alloying metals, which can be considered as a whole, preferably Ca, Sn, Si, In, Bi, Mn, K, Sr, Ba and mixtures thereof, more preferably Ca, Sn, Si, In, Bi and mixtures thereof.
[0041] The balance of the alloy is formed by zinc and unavoidable impurities.
[0042] Preferably, the zinc alloy comprises 87.0-98.0% by weight of zinc, 0.0-10.0% by weight, preferably 2.0-8.0% by weight of aluminum and 0.0-6.0% by weight of magnesium or mixtures thereof, each relative to the total amount of metals in the zinc alloy. In a further preferred embodiment, the proportion of Sn, Ca, Si, In, Bi, Mn, K, Sr, Ba and mixtures thereof is less than 0.3% by weight, more preferably less than 0.1% by weight, in each case based on the total amount of the zinc alloy. Any alloy as well as particles based on pure zinc may also contain naturally occurring unavoidable impurities of the corresponding metal components.
[0043] Term c Zn,M represents the amount of elemental zinc and optionally additional elemental alloying metal (M), which can be determined by volumetric titration. The volumetric titration is based on the reduction of Fe(III) ions to Fe(II) ions and the simultaneous oxidation of the elemental metal, which is described in detail in the experimental section below. The Fe(II) ions can be titrated with potassium permanganate or with cerium. In the case of other metal alloying components M, it is necessary to first determine the composition of the alloy (for example by X-ray diffraction) and then calibrate the titration result under the assumption that all metal elements are uniformly oxidized. The content of elemental zinc c Zn,M It is in the range of 58.0-85.0 wt. %, in a preferred embodiment in the range of 59.0-80.0 wt. %, in a most preferred embodiment in the range of 60.0-78.0 wt. %, each relative to the composite material.
[0044] Amounts below 58.0 wt. % are too low, resulting in insufficient corrosion performance in corrosion films and insufficient durability when used as sacrificial anodes. Above 85.0 wt. %, the color of the composite is not dark enough and may also cause safety issues due to the high amount of elemental metal, which is at least partially present in finely divided form, while the amount of the corresponding metal oxide is relatively low.
[0045] Without being bound by any theory, it is assumed that the zinc or zinc alloy is present at least partially as nanoparticles with an average particle size of less than 60 nm, preferably less than 50 nm. Such metal nanoparticles can be well embedded in the Zn-oxide and / or the additional material c). It is assumed that the presence of such nanoparticles is largely responsible for the black color of the composite material particles.
[0046] The Zn-oxide as component b) is in most cases derived from the oxidation of zinc particles. The preparation of these particles involves dry grinding of zinc powder under harsh conditions, which results in a significant amount of zinc being oxidized. After the grinding process, the composite material particles come into contact with the ambient atmosphere, which generally causes further oxidation on the particle surface.
[0047] The term "Zn-oxide" in this context represents the oxide ZnO, the hydroxide Zn(OH)2 and any mixture of oxides and hydroxides of Zn, wherein the formal oxidation state of zinc can be between (0) and (II), preferably between (I) and (II). In particular, such mixed substances can be produced on the surface of the black particulate zinc composite material under the influence of oxygen and water during and after the grinding process.
[0048] In the case of zinc alloys, other metal components, such as aluminum or magnesium, may also be partially oxidized. The amount of these oxides can be simply determined by first measuring the content c Zn,M The residual amount of organic lubricants such as fatty acids can be corrected by estimating the content of α-amino-2-nitropropene and additional material c) and then subtracting these contents from the total amount of black composite particles.
[0049] Another method for determining the Zn-oxide content consists in detecting the total content of zinc (including possible alloying metals) by titrating the black particle composite material with EDTA in a hydrochloric acid medium, as described in paragraph
[0063] of JP2020105575A, and recalculating the amount of ZnO by subtracting the elemental metal content determined by Fe(II) oxidation (in combination with potassium permanganate titration or cerium titration).
[0050] Component b) Content of ZnO (and possibly other metal oxides derived from alloy components) c ZnO,M-oxIt is preferably in the range of 10.0-35.0 wt %, more preferably in the range of 13.0-34.0 wt %, most preferably in the range of 15.0-32.0 wt %, each relative to the total amount of the composite material particles.
[0051] A portion of the Zn-oxide will be located on the surface of the black zinc pigment, while the other portion will be in the interior of the particles at least partially admixed with the elemental metal.
[0052] In a preferred embodiment, at least 30 atomic %, more preferably at least 40 atomic % and most preferably at least 50 atomic % of the total Zn-oxide content is found in the interior of the particles, relative to the total Zn-oxide content.
[0053] These amounts can be determined by examining cross sections of black zinc particles by SEM (scanning electron microscopy) in combination with EDX (energy dispersive X-ray spectroscopy).
[0054] The additional material c) serves as a grinding aid during the grinding of the zinc powder in the dry grinding process.
[0055] The additional material c) is a material with a specific hardness, since it is used as a grinding aid during the dry grinding process. The additional material preferably has a hardness in the range of more than 2.5 to about 9.5, more preferably in the range of 4 to 7, as assessed according to the Mohs scale. The hardness values refer to the corresponding bulk material. The hardness must be higher than the hardness of elemental zinc (2.5) in order to be able to grind zinc powder. However, the hardness should not be too high, since the interior of the ball mill or the beads could be adversely affected or even destroyed by the material.
[0056] The grinding aid strongly causes deformation of the zinc powder particles and itself has no change in particle morphology or can be broken into smaller parts. In the final black zinc particles, the material is admixed with elemental zinc and optionally with ZnO.
[0057] After the entire production process, the additional material c) is preferably at least partially admixed with the elemental zinc particles. The admixed grinding aid can also be detected by examining the cross section of the black zinc particles by SEM combined with EDX. The admixed particles are found in the interior of these particles.
[0058] Preferably at least 50 atomic %, more preferably at least 60 atomic %, even more preferably at least 70 atomic %, and most preferably at least 80 atomic % of the grinding aid is admixed with the elemental zinc particles.
[0059] It was found that after the grinding process, only a small portion of the grinding aid may be on the surface of the composite material particles.
[0060] The additional material c) does not form an encapsulating coating or a coating of discrete particles on the surface of the zinc particles. Particles of said material c) may occasionally be present on the surface of the zinc composite particles, but preferably less than 20% by mass of the material c) is present in this form.
[0061] Preferably, the additional material c) is selected from the following group:
[0062] i) metal oxides or metal hydroxides, for example SiO2, TiO2, Al2O3, Al(OH)3, magnetite, Fe2O3, ZrO2 and mixtures thereof, or
[0063] ii) silicates or aluminosilicates, for example synthetic mica, natural mica, preferably biotite or muscovite, nepheline syenite, zinc silicate and mixtures thereof;
[0064] iii) metal phosphates,
[0065] iv) BaSO4, or a mixture of any of the above i) to iv).
[0066] The material c) should have a compact form, such as spherical, flake or unformed. Needle-shaped forms should be avoided. Typically, the material c) is selected from inorganic metal oxide pigments, fillers or desiccants commonly used in the coatings industry.
[0067] In a specific embodiment, the material c) may also comprise ZnO or consist of ZnO. These ZnO particles may also be mixed with any of the above-mentioned additional materials c).
[0068] In the most preferred embodiment, the additional material c) is SiO2 or nepheline syenite or a mixture thereof.
[0069] The additional material c) may be surface-modified, in particular hydrophobized. The hydrophobization may be achieved, for example, by organofunctional silanes having alkyl or aryl moieties.
[0070] Most preferably, hydrophobized SiO2 or hydrophobized nepheline syenite or a mixture thereof is used as additional material c).
[0071] Examples of organofunctional silanes for hydrophobizing the additional material c) are dimethyldichlorosilane, trimethoxy-isobutylsilane, trimethoxyoctylsilane, hexadecyltrimethoxysilane, octyltriethoxysilane; silazanes selected from 1,1,1-trimethyl-N-trimethylsilyl-silylamine and N-methyl-aza-2,2,4-trimethylsilacyclopentane; or siloxanes selected from octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane or polydimethylsiloxane; and combinations thereof.
[0072] Examples of commercially available products used as additional material c) are amorphous silicon dioxide particles, for example Syloid Al 1 (Grace), amorphous or precipitated silicon dioxide particles, for example Aerosil R 972 or Aerosil 9201 from Evonik, Sipernat D10, Sipernat D13 or Sipernat D14. Examples of nepheline syenites are the Minex products from Sibelco (Belgium) or the Silibond or Treminex products from Quarzwerke Group (Germany). Examples of BaSO4 are Blanc Fixe N or G from Solvay. Examples of metal phosphates are products, such as ZnCaSrAl orthophosphate silica hydrate, such as ZCPPlus, or modified zinc orthophosphate such as ZPO.
[0073] According to the present invention, the content of the additional material c) is referred to as c add , is in the range of 4.5-17.0 wt %, preferably in the range of greater than 4.5 wt % to 15.0 wt %, more preferably in the range of 5.0-14.0 wt %, most preferably in the range of 6.0-13.0 wt %, each relative to the total amount of the composite material. Suitable preferred ranges are also 6.0-17.0 wt % and 7.0-17.0 wt %, each relative to the total amount of the composite material.
[0074] When the amount is less than 4.5 wt %, the degree of blackness will be too low; when the amount is more than 17 wt %, the anticorrosion effect will be too low because the amount of active Zn is too low.
[0075] Content of grinding aid additives c add and the content of metal oxides c ZnO,M The sum of is preferably in the range of 15.0-42.0 wt. %, more preferably in the range of 20.0-41.0 wt. %, most preferably in the range of 22.0-40.0 wt. %, each relative to the total amount of the black particulate zinc composite material.
[0076] The elemental content of zinc and optionally other metal alloy components present in the composite is c Zn,M represents the cathode mass that can be obtained when the pigment is used as a sacrificial anode. However, since the pigment has a very high specific surface area, the cathode mass is more easily achieved. This can be expressed as the specific active Zn content c Zn,M,spec. The parameter is defined as c Zn,M,spec =c Zn,M / BET.
[0077] The term "BET" herein refers to the specific surface area measured by a well-known method based on the Brunauer-Emmett-Teller (BET) theory, wherein a three-point detection method is adopted and nitrogen is used as the adsorption gas. Zn,M,spec is 14.0-87.0 wt% xg / m 2 In the range of 15.0-87.0 wt% xg / m 2 In the range of 20.0-87.0 wt% xg / m 2 In the range of 21.0-70.0 wt% xg / m 2 In the range of 23.0-65.0 wt% xg / m 2 within the range.
[0078] The particle size can be measured by laser granulometry, preferably using a Malvern Mastersizer 2000 device. As a measure of the average diameter, the median d 50 These particle sizes are measured as volume-weighted spherical equivalents according to the Fraunhofer approximation and according to the manufacturer's guidelines for the testing instrument. Preferably, the d 50 In the range of 5.0-30 μm, more preferably in the range of 6.5-30 μm, even more preferably in the range of 7-30 μm, further more preferably in the range of 8-27 μm, most preferably in the range of 9-25 μm.
[0079] When 50 Below 5.0 μm, the particles become too fine to cause safety issues when finally dried into powders. In addition, they can cause viscosity issues when formulated into coating formulations, thereby limiting the formulation flexibility of the anticorrosive pigment.
[0080] When 50 Above 30 μm, these particles are difficult to obtain due to the harsh preparation conditions.
[0081] Preparation method:
[0082] The method for preparing the black zinc composite material comprises the following steps:
[0083] a) providing a mixture comprising zinc powder, a grinding aid and a lubricating aid in a grinding agglomerate provided with grinding balls, said grinding aid being prepared from the additional material c),
[0084] b) dry grinding the mixture obtained in step a) for a period of time t m , wherein no fluorocarbon polymers are used in the grinding process,
[0085] c) separating the ground mixture from the ground agglomerates, and
[0086] d) Optionally carrying out further steps, such as particle classification and / or pasting.
[0087] In this process, the zinc powder used preferably has an approximately spherical geometry. The zinc powder obtained after melt atomization preferably has a median particle diameter d in the range from 2 μm to 500 μm. 50,粉末 , more preferably 5 μm to 200 μm, even more preferably 10 μm to 100 μm. Preferably, the metal powder obtained by atomization has a narrow particle size distribution. Preferably, the spherical metal particles used in the alloy of the present invention have D 10 The value is 1 μm to 15 μm, preferably 1.0 to 10 μm, D 50 The value is 25 μm to 75 μm, preferably 30 μm to 40 μm, D 90 The value is 75 μm to 90 μm, preferably 80 μm to 90 μm.
[0088] The dry grinding process is carried out under very harsh conditions. The grinding time t m Preferably it is in the range of 12 to 36 hours, more preferably in the range of 13 to 30 hours, most preferably in the range of 15 to 24 hours. These grinding times are usually significantly longer than conventional grinding times for producing zinc flakes, for example.
[0089] It is important to use additives as grinding aids in the grinding process.
[0090] Grinding aids are also referred to herein as "grinding aid additives".
[0091] Grinding aids promote the formation of very fine zinc or zinc alloy particles. These fine particles are assumed to be dark gray to black. Due to the harsh conditions of the grinding process, grinding aids can also be ground and eventually blended with elemental zinc or zinc alloy. Grinding aids also make the zinc powder less cold-fused compared to conventional grinding of zinc powder without the use of grinding aids.
[0092] The grinding process is preferably carried out under conditions of low oxygen content compared to ambient conditions. For example, the grinding atmosphere may contain 3-15% oxygen in an inert gas atmosphere, such as nitrogen or argon.
[0093] The zinc metal or zinc alloy metal component will be partially oxidized during the grinding process. After the grinding process, the mixed black pigment will further come into contact with oxygen or water under ambient conditions and form metal oxides on its surface. However, a portion of metal oxides may be formed during the grinding process, especially for small zinc particles, so it will also be mixed with elemental zinc metal.
[0094] The average particle size of the grinding aid particles used before grinding is d 50,研磨 Preferably, it is in the range of 0.05-12 μm, more preferably in the range of 1.0-8.0 μm. These particle sizes refer to the initial particle size, not to the aggregates separated or crushed during the grinding process. The particles used as grinding aids can also be at least partially crushed, so that the final median particle size is mostly smaller than the initial particle size.
[0095] Preferably, the amount of grinding aid additive is 4.5-17.0 wt. %, more preferably 6.0-13.0 wt. %, each based on the amount of zinc powder. When the amount is below 4.5 wt. %, the particles formed are not black enough. If the amount is greater than 17 wt. %, the amount of elemental zinc or elemental alloy metal will be too low.
[0096] The grinding aid is preferably selected from the group consisting of:
[0097] i) selected from metal oxides or metal hydroxides, for example SiO2, TiO2, Al2O3, Al(OH)3, magnetite, Fe2O3, ZrO2 and mixtures thereof, or
[0098] ii) selected from silicates or aluminosilicates, for example synthetic mica, natural mica, preferably biotite or muscovite, nepheline syenite, zinc silicate and mixtures thereof;
[0099] iii) metal phosphates,
[0100] iv) BaSO4, or a mixture of any of the above i) to iv).
[0101] Preferably, the grinding aid is at least partially admixed with the elemental zinc particles after the entire preparation process. The admixed grinding aid can be detected by examining the cross-section of the black zinc particles by SEM combined with EDX. The admixed particles are found to be inside these particles.
[0102] Preferably, at least 50 atomic %, more preferably at least 60 atomic %, even more preferably at least 70 atomic %, and most preferably at least 80 atomic % of the grinding aid is admixed with the elemental zinc particles.
[0103] It was found that after the grinding process, only a small portion of the grinding aid may be on the surface of the composite material particles.
[0104] Other components of the grinding mixture are lubricants, such as fatty acids. Preferably, saturated fatty acids are used as lubricants, such as stearic acid, oleic acid, linoleic acid, ricinoleic acid, palmitic acid, arachidic acid, myristic acid, lauric acid, capric acid, elaidic acid, erucic acid, linolenic acid, myristic acid, palmitoleic acid and mixtures thereof. Most preferably, saturated fatty acids are used, such as palmitic acid, stearic acid and mixtures thereof.
[0105] Preference is given to using fatty acids with unbranched alkyl groups. In this case, at least 90% of the fatty acids are unbranched, while up to 10%, preferably up to 4% and most preferably up to 2% of the fatty acids may be branched.
[0106] After the preparation process, the content of these well-known lubricants is usually very low, preferably in the range of 0.1-3.0 wt. %, more preferably in the range of 0.2-2.5 wt. %, even more preferably in the range of 0.3-2.0 wt. %, most preferably in the range of 0.5-1.0 wt. %, each based on the total amount of zinc metal or zinc alloy and the grinding aid. Such low content promotes the formation of black composite zinc pigments, in which the grinding aid additives and part of the formed metal oxide are admixed with the elemental metal.
[0107] Dry grinding processes are advantageously used over wet grinding processes because no solvent needs to be used (avoiding solvent release) and the process is more energy efficient.
[0108] The grinding agglomerate is preferably any kind of grinding media mill, such as a ball mill or impact mill suitable for dry grinding, a pin mill, a blast mill, a beater mill or an attrition disk mill. These mills are commercially available, for example, from the German company Netzsch.
[0109] The grinding balls of the ball mill are preferably made of steel and have a diameter of about 2.5 to about 6.0 mm. When the diameter is below 2.5 mm, the energy of the grinding is too low; and when the diameter is above 6.0 mm, the pulverization of the zinc powder is not optimal.
[0110] The number of rotations is preferably about the critical number of rotations n crit The range of 55% to 75% can be determined according to the well-known formula:
[0111]
[0112] Where D is the diameter of the drum and g is the gravitational constant.
[0113] More preferably, the rotation number is in the range of 60% to 70% with respect to the critical rotation number.
[0114] When the number of rotations is less than 55%, the energy input to the abrasive is too low, and when the number of rotations is more than 75%, the workability becomes poor.
[0115] According to the present invention, no fluorocarbon polymer is used during the grinding process. More particularly, no fluorocarbon polymer such as PTFE is used as a lubricant in the dry grinding process. According to US 7,023,572 B2, non-black zinc flakes can be prepared by using a fluorocarbon polymer as a lubricant and using a cooled ball mill.
[0116] The black particulate zinc composite material can be used in a heavy corrosion protection formulation, which is particularly applied to automobiles and structures, especially buildings and bridges, etc. Particularly preferably, the spin-on dip-coating formulation can be preferably used to coat screws, especially in automotive applications. In particular in automotive applications, this formulation can be used to coat clips, washers, metal plates, screws, bolts, buckles, brakes or auto chassis parts.
[0117] Other aspects:
[0118] In addition, in some embodiments, material c) comprises ZnO or Zn(OH) 2 or a mixture thereof, or consists of it. For these specific embodiments, the present invention has the following aspects:
[0119] A first aspect relates to a black particulate zinc composite material comprising:
[0120] a) Elemental zinc or zinc alloy, containing c Zn,M is in the range of 58.0-85.0 wt % relative to the composite material,
[0121] b) Zn oxide,
[0122] Component b) is at least partially admixed with the elemental zinc or zinc alloy metal a).
[0123] The second aspect according to the first aspect relates to a black particle zinc composite material, wherein the content c Zn,M It is in the range of 60.0-75.0 wt % relative to the composite material.
[0124] A third aspect according to any one of the above aspects relates to a black particulate zinc composite material, wherein the specific active Zn content c Zn,spec. Defined as c Zn,spec =c Zn / BET, and 14.0-90 wt% xg / m 2 within the range.
[0125] A fourth aspect according to any one of the above aspects relates to a black particulate zinc composite material, wherein the specific active Zn content c Zn,spec 25-87 wt% xg / m 2 within the range.
[0126] A fifth aspect according to any one of the above aspects relates to a black composite material, wherein the component a) is a zinc alloy represented by the following formula:
[0127] ZnAl x Mg y M f z (I)
[0128] wherein x, y and z represent the weight % content of the corresponding metal relative to the total content of the alloy, and
[0129] Where x is in the range of >0 to 10, y is in the range of >0 to 7, z is in the range of 0 to 0.5, and where M f represents other metals, which may be considered as a whole and are selected from Ca, Sn, Si, In, Bi, Mn, K, Sr, Ba and mixtures thereof.
[0130] A sixth aspect according to any one of the above aspects relates to a black composite material, wherein when a cross section is analyzed using SEM and EDX, at least 15 mol % of ZnO, Zn(OH) 2 or a mixture thereof as component b) is found inside the composite material.
[0131] A seventh aspect according to any one of the above aspects relates to a black particulate zinc composite material, wherein b) the content of Zn-oxide is in the range of 15.0-42.0 wt. % relative to the total amount of the composite material.
[0132] An eighth aspect according to any of the above aspects relates to a black composite material, wherein at least a portion of the ZnO or Zn(OH) 2 is used as a grinding aid during the grinding of zinc powder in a dry grinding process.
[0133] A ninth aspect relates to a method for preparing a black composite material, comprising the following steps:
[0134] a) providing a mixture comprising zinc powder or zinc alloy powder, a grinding aid and a lubricating aid in a grinding agglomerate equipped with grinding balls, wherein the grinding aid is prepared from ZnO, Zn(OH)2 particles or a mixture thereof,
[0135] b) dry grinding the mixture obtained in step a) for a period of time t m ,
[0136] c) separating the ground mixture from the ground agglomerates, and
[0137] d) Optionally carrying out further steps, such as particle classification and / or pasting.
[0138] A tenth aspect according to aspect 9 relates to a method for preparing a black composite material, wherein the amount of the grinding aid used is 4.5-17.0 wt % based on the amount of zinc powder.
[0139] The eleventh aspect according to aspect 9 or 10 relates to a method for preparing a black composite material, wherein the median particle size d 50,研磨 It is in the range of 0.05 to 12 μm.
[0140] A twelfth aspect according to any one of aspects 9 to 11 relates to a method for preparing a black composite material, wherein the grinding time t m In the range of 12-36 hours.
[0141] A thirteenth aspect according to any one of aspects 9 to 12 relates to a method for preparing a black composite material, wherein the zinc alloy powder is represented by the following formula:
[0142] ZnAl x Mg y M f z (I)
[0143] wherein x, y and z represent the weight % content of the corresponding metal relative to the total content of the alloy, and
[0144] Where x is in the range of >0 to 10, y is in the range of >0 to 7, z is in the range of 0 to 0.5, and where M f represents other metals, which may be considered as a whole and are selected from Ca, Sn, Si, In, Bi, Mn, K, Sr, Ba and mixtures thereof. Example
[0145] Embodiment 1:
[0146] 7 kg of steel balls (diameter: 4.7 mm), 180 g of zinc alloy 1 powder <140 μm, 20 g of grinding aids according to Tables 1 and 2 and 1 g of stearic acid were added to a barrel mill (length: 35 cm, width: 18 cm). The mixture was then dry ground at 60 rpm with a lower oxygen content of 5% for 16 hours. The product was then saturated with an increased oxygen content for 2 hours. Finally, the resulting black zinc composite product was carefully separated from the metal balls using a sieve.
[0147] Embodiment 2:
[0148] 7 kg of steel balls (diameter: 4.7 mm), 180 g of zinc alloy 1 powder <140 μm, 20 g of grinding aids according to Tables 1 and 2 and 2 g of stearic acid were added to a barrel mill (length: 35 cm, width: 18 cm). The mixture was then dry ground at 60 rpm with a lower oxygen content of 5% for 16 hours. The product was then saturated with an increased oxygen content for 2 hours. Finally, the resulting black zinc composite product was carefully separated from the metal balls using a sieve.
[0149] Examples 3 to 24 and Comparative Examples 1 to 5:
[0150] The other examples were carried out as described in Example 1 or 2, but using the test parameters shown in Table 1. In Table 2 the grinding aid additives used are listed in more detail.
[0151] Comparative Example 6:
[0152] Black Zinc Competitors Zinc Z2031 (Benda-Lutz, from Sun Chemical Company).
[0153] Initial zinc powder:
[0154] Some embodiments of the present invention use commercially available Zinc (Zinc) AS <45 μm (Eckart Suisse) was used as the initial zinc powder, as shown in Table 1.
[0155] In other examples, zinc alloys with a generally spherical geometry obtained by conventional atomization were used (referred to as "zinc alloy 1 or 2" in Table 1). The composition of zinc alloy 1 was 94% by weight zinc, 5% by weight aluminum, and 1% by weight magnesium. Different proportions of this alloy were used, as shown in the sieving or air classification parameters in Table 1.
[0156] The composition of the zinc alloy 2 is 6 wt % of aluminum, 6 wt % of magnesium, and the balance of zinc.
[0157] Table 1: Experimental parameters for the preparation examples
[0158]
[0159] *In this example, the oxygen content is 12% by volume instead of 5% by volume. **In these examples, the ball size is 4 mm instead of 4.7 mm.
[0160] Table 2: Grinding aid additives used for grinding in Examples and Comparative Examples
[0161]
[0162] Characterization:
[0163] The particle sizes of the examples and comparative examples were characterized and tested using various methods. The results are shown in Table 3.
[0164] Detection particle size:
[0165] About 0.5 g of black zinc pigment from the sample was dispersed with isopropanol in a Hydro 2000G dispersing device and then tested with a connected Malvern Mastersizer 2000 according to the manufacturer's information, during which time the test was carried out in the test chamber under ultrasonic impact. The particle size was determined according to the Fraunhofer approximation method based on the volume weighted size of an equivalent sphere. Median d 50 Used as a measure of average particle size.
[0166] Preparation of plates for corrosion testing & color detection:
[0167] 56.5 g of the black pigment of the examples of the invention and the comparative example are slowly stirred into 43.5 g of a solvent-based silicate varnish having a solid content of about 55% by weight and then dispersed. Optionally, the viscosity is adjusted to a range of 30 s to 50 s, the viscosity being measured using a flow cup according to DIN 53211, dipropylene glycol (up to 10 g) is added and the varnish is applied to a metal substrate (steel Q-Panel R46) by the draw-down method (nominal dry film applied: 24 μm, speed 3 cm / min), with two applications in opposite directions. The panels are ventilated at 100° C. for about 30 minutes, then cooled and placed in an oven at 300° C. for 40 minutes. After cooling, the panels can be used for color testing and salt spray tests.
[0168] Salt spray test:
[0169] Now, the painted metal sheets are subjected to a salt spray test according to ASTM B117, ISO 9227 or ASTM G85 to investigate their rust resistance. The red rust formed after 504 hours is evaluated as a percentage of the entire exposed area. When the red rust area is ≤1.5%, it is considered to pass the test. If the red rust area is ≤0.8%, it is indicated as "++"; if the red rust area is greater than 0.8% and ≤1.5%, it is indicated as "+". If the red rust area is >1.5% and ≤10.0, it is indicated as "-"; and if the red rust area is >10.0%, it is indicated as "--".
[0170] Detect color:
[0171] The painted panels were also used to measure the color on a Minolta 700d spectrophotometer. The diffuse L* value was measured using the D65 / 10° condition. The 4 corners and the center point of each panel were measured in a clockwise direction. 10 test results were taken from each point and the average was calculated. An L* value of about 32 corresponds to the visual appearance of carbon black. Samples with an L* value <29.0 are indicated as "++", samples with an L* value ≥29.0 and <34.0 are indicated as "+", and samples with an L* value ≥34.0 do not meet the test and are indicated as "-".
[0172] Detection of active zinc content (for pure zinc compounds):
[0173] The active zinc content was determined by volumetric titration.
[0174] The zinc pigment sample was dispersed into the ferric sulfate solution to convert Fe 3+ ions are reduced to Fe 2+ These Fe 2+ The ions were titrated with potassium permanganate solution (0.1 N).
[0175] In the first step, the titer of potassium permanganate is tested. Therefore, about 0.5 g of sodium oxalate is weighed and added to a 250 ml beaker, dissolved in distilled water, and added to a 250 ml volumetric flask until the mark. Then, 50 ml of this solution is added to a conical flask using a pipette. Fill a 25 ml burette with potassium permanganate (0.1 N) and adjust the zero point. Heat the sodium oxalate solution to 50 ° C with stirring and then titrate with potassium permanganate solution. The volume required at this time is V1, in ml. The titer of the potassium permanganate solution is calculated as follows:
[0176]
[0177] A blank test is performed as follows: 5 ml of acetone is placed in a conical flask, then 50 ml of ferrous sulfate solution is added, followed by about 30 ml of sulfuric acid (30%). Then 2 or 3 drops of potassium permanganate are added to the solution and swirled. If the color of the potassium permanganate remains unchanged, the Fe solution and acetone are not defective.
[0178] To test the zinc content, weigh 100 mg of zinc sample and add it to a 250 ml conical flask. To better disperse the zinc particles, add 5 ml of acetone and heat slightly. Then, add 50 ml of ferric sulfate solution with a suitable concentration and stir gently until the solid is dissolved. After adding 30 ml of sulfuric acid (30%), the color turns slightly green. The solution is titrated with potassium permanganate solution to obtain a volume V2 in ml.
[0179] The active zinc content is calculated accordingly as follows:
[0180]
[0181] For better reproducibility, the titration was repeated several times (2 to 3 times) and the results were averaged. In the case of zinc alloys containing Al and Mg, the elemental metal content c, ZnM The measurement must be calibrated with the calibration factor k1 defined as follows:
[0182]
[0183] Among them, M Zn 、M Al and M Mg is the corresponding molar mass, M 合金 is the effective molar mass of the alloy, x is the weight % content of Al in the zinc alloy, and y is the weight % content of Mg in the zinc alloy.
[0184] This calibration factor is based on the assumptions that the particles are homogeneous in elemental metal content, that alloying elements do not segregate, that oxidation during milling is uniform for the metals, and that no composition shifts occur during titration.
[0185] Table 3: Test data and results:
[0186]
[0187]
[0188] List of Figures:
[0189] Figure 1 : Comparison photos of the flat plate in the salt spray test after 504 hours:
[0190] Upper row: Comparative Example 6; Lower row: Example 2. The three plates used for each sample were located at different positions in the salt spray chamber and therefore slightly different.
[0191] Figure 2 : SEM micrograph of a cross section of the pigment described in Example 3, at a magnification of 10,000.
[0192] discuss:
[0193] All zinc pigment samples of Examples 1 to 24 of the present invention have sufficiently dark colors (L*<34.0) and successfully pass the salt spray test. Comparative Example 6 of a commercial product also has sufficiently dark colors, but fails the salt spray test, as shown in FIG. Figure 1 It is clearly visible that at any time point shown, the plate of Example 2 is significantly smoother than the plate of Comparative Example 6, where the red rust areas in the black and white photograph appear as dark colors ("holes").
[0194] However, other differences can be seen: in comparative example 1, glass flakes were used as grinding aids, and the pigment of comparative example 1 was not dark enough and did not pass the salt spray test. All other comparative examples were dark enough, but did not pass the salt spray test. In particular, comparative examples 2 to 5 were carried out using pure zinc powder, different additives and a very long grinding time of 1200 minutes. The active zinc content of these samples was quite low. In comparison with these tests, examples 12 to 14 were carried out under comparable conditions, but using zinc alloys. These results show that zinc alloys are more advantageous than pure zinc.
[0195] Overall, all examples using silica or nepheline syenite compounds as grinding aids show excellent results. ZnO or TiO2 particles can also be used as grinding aids, but longer grinding times (Examples 22 and 23) or higher concentrations (Example 24) should be used.
[0196] exist Figure 2 In the SEM micrograph of the cross section, the internal structure of the pigment described in Example 3 can be seen. Here, the silicon dioxide particles used as a grinding aid appear darker than the zinc or zinc oxide. It is clearly visible that the majority of the silicon dioxide particles are inside the pigment and are therefore admixed with the zinc or zinc oxide.
Claims
1. A black particle zinc composite material comprising: a) Elemental zinc or zinc alloy, containing c Zn,M is in the range of 58.0-85.0 wt % relative to the composite material, b) Zn-oxide, and c) additional material, wherein the content of the additional material c) is c add is in the range of 4.5-17.0 wt % relative to the total weight of the composite material, And wherein components b) and c) are at least partially admixed with said elemental zinc or zinc alloy metal a).
2. The black particle zinc composite material according to claim 1, wherein the additional material c) is selected from the group consisting of: i) a metal oxide or a metal hydroxide selected from SiO2, TiO2, Al2O3, Al(OH)3, magnetite, Fe2O3, ZrO2 and mixtures thereof, or ii) a silicate or aluminosilicate selected from synthetic mica, natural mica, preferably biotite or muscovite, nepheline syenite, zinc silicate and mixtures thereof; iii) metal phosphates, iv) BaSO4, or a mixture of any of the above i) to iv).
3. The black particulate zinc composite material according to any one of the preceding claims, wherein the additional material c) is SiO2 or nepheline syenite or a mixture thereof.
4. The black particulate zinc composite material according to claim 3, wherein the additional material c), preferably SiO2, is further hydrophobized.
5. The black particulate zinc composite material according to any one of the preceding claims, wherein the content of the additional material c) is in the range of 6.0-17.0 wt% relative to the total weight of the composite material.
6. The black particulate zinc composite material according to any one of the preceding claims, wherein c Zn,M It is in the range of 59.0-80.0 wt%.
7. The black particulate zinc composite material according to any one of the preceding claims, wherein the total amount of b) Zn-oxide and additional material c) is in the range of 15.0-42.0 wt. % relative to the total amount of the composite material.
8. The black particulate zinc composite material according to any one of the preceding claims, wherein the specific active Zn content c Zn,spec. Defined as c Zn,spec =c Zn / BET, and 14.0-87.0 wt% x g / m 2 within the range.
9. A black particulate zinc composite material according to any one of the preceding claims, wherein the additional material c) does not form a coating or a coating of discrete particles on the surface of the zinc particles.
10. The black particulate zinc composite material according to any one of the preceding claims, wherein d 50 It is in the range of 6.5 to 30 μm.
11. The black particle zinc composite material according to any one of the preceding claims, wherein the component a) is a zinc alloy represented by the following formula: ZnAl x Mg y M f z (I) wherein x, y and z represent the weight % content of the corresponding metal relative to the total content of the alloy, and Where x is in the range of >0 to 10, y is in the range of >0 to 7, z is in the range of 0 to 0.5, and M f represents other metals which may be considered as a whole and are selected from Ca, Sn, Si, In, Bi, Mn, K, Sr, Ba and mixtures thereof.
12. The black particulate zinc composite material according to any one of the preceding claims, wherein the additional material c) is used as a grinding aid during the grinding of zinc powder in a dry grinding process.
13. The black particulate zinc composite material according to any one of the preceding claims, wherein the composite material exhibits an L* value of <34.
0.
14. A method for preparing the black particle zinc composite material according to any one of claims 1 to 13, comprising the following steps: a) providing a mixture comprising zinc powder or zinc alloy powder, a grinding aid and a lubricating aid in a grinding agglomerate provided with grinding balls, wherein the grinding aid is prepared from the additional material c), b) dry grinding the mixture obtained in step a) for a period of time t m , wherein no fluorocarbon polymers are used in the grinding process, c) separating the ground mixture from the ground agglomerates, and d) Optionally carrying out further steps, such as particle classification and / or pasting.
15. The method according to claim 14, wherein the grinding aid is selected from the group consisting of: i) a metal oxide or a metal hydroxide selected from SiO2, TiO2, Al2O3, Al(OH)3, magnetite, Fe2O3, ZrO2 and mixtures thereof, or ii) a silicate or aluminosilicate selected from synthetic mica, natural mica, preferably biotite or muscovite, nepheline syenite, zinc silicate and mixtures thereof; iii) metal phosphates, iv) BaSO4, or a mixture of any of the above i) to iv).
16. Use of the black particulate zinc composite material according to any one of claims 1 to 13 as an anticorrosive pigment in a heavy corrosion protection formulation.
Citation Information
Patent Citations
Corrosion protection coating agent for creating dark surfaces and workpieces with this corrosion protection coating agent
DE102014105434A1
Dark pigments reflecting IR radiation, method for the production thereof, and use thereof
EP2173819A2
Method for manufacturing scaly zinc powder
JP2020105338A
Black zinc dust and method for producing the same
JP2020105575A
Black zinc powder and method for producing the same
JP2021038331A
